If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(x + 3) = log(x + -3) + 1.5 Reorder the terms: glo(3 + x) = log(x + -3) + 1.5 (3 * glo + x * glo) = log(x + -3) + 1.5 (3glo + glox) = log(x + -3) + 1.5 Reorder the terms: 3glo + glox = glo(-3 + x) + 1.5 3glo + glox = (-3 * glo + x * glo) + 1.5 3glo + glox = (-3glo + glox) + 1.5 Reorder the terms: 3glo + glox = 1.5 + -3glo + glox Add '-1glox' to each side of the equation. 3glo + glox + -1glox = 1.5 + -3glo + glox + -1glox Combine like terms: glox + -1glox = 0 3glo + 0 = 1.5 + -3glo + glox + -1glox 3glo = 1.5 + -3glo + glox + -1glox Combine like terms: glox + -1glox = 0 3glo = 1.5 + -3glo + 0 3glo = 1.5 + -3glo Solving 3glo = 1.5 + -3glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '3glo' to each side of the equation. 3glo + 3glo = 1.5 + -3glo + 3glo Combine like terms: 3glo + 3glo = 6glo 6glo = 1.5 + -3glo + 3glo Combine like terms: -3glo + 3glo = 0 6glo = 1.5 + 0 6glo = 1.5 Divide each side by '6lo'. g = 0.25l-1o-1 Simplifying g = 0.25l-1o-1
| 3x^2+4-7x=0 | | B+63=19 | | -4=p+12 | | ln(x+3)=ln(x-3)+1.5 | | 4tanx=10 | | 8b+3=b | | 16+11h=9h | | 8x+26=4x+2 | | 7y-8=4y+31 | | (7x-68)=(-3+110) | | 6x+26=8x+12 | | 3y+-1=7 | | (3x-10)=(3x-2) | | 3x^2+y^2=4 | | M^2+8+16=0 | | 3y+2ln(x)=4ln(y+7) | | (-3+106)=(7x-64) | | (5x+49)=(3x+57) | | 8sin^2x-7=-2cosx | | 10x+4y=52 | | 10x-4y=52 | | F(9)=4(9)-2 | | 3sint-sint=0 | | cos^10x-sin^10x=1 | | 3x+5x=6x | | sqrt(x+15)+15=-sqrt(x) | | 192/4=x/1 | | 1.79266204420746E-308=0 | | X=-4t+2t^2 | | 75=5x^2-20x | | z+y=1 | | (x+17)(x-22)=0 |